Pelatihan Mendeley dalam Mengelola Referensi Karya Ilmiah Mahasiswa di Institut Sunan Giri Ponorogo - mujahada, kharis (STAI Terpadu Yogyakarta, 2023)
Community Service activities carried out by STAI Terpadu Yogyakarta Lecturers are providing training on the use of the Mendeley Application, especially in finding and writing references and bibliography. The purpose of holding this training for students of the Early Childhood Islamic Education Study Program (PIAUD) and Islamic Religious Education (PAI) is to improve skills in applying the mendeley application in writing scientific papers. The main problem faced by students at Insuri Ponorogo is being able to operate the mendeley application. The method used to overcome this problem is by organizing training activities with a total of 50 students with 25 from PAUD and 25 others from PAI. Dissemination of information about the training was conveyed through social media, whatsapp groups, and circulars on campus. The result of the activity is that students successfully participate in the activity enthusiastically until the end of the program and students are able to operate the mendeley application in writing scientific papers at the end of their studies. It is hoped that this training opportunity will be given to all Insuri Ponorogo students on an ongoing basis so that knowledge and skills in the field of writing scientific papers will always continue to increase